The Influence of Social-Emotional Development on Early Childhood Learning Outcomes During the Covid-19 Pandemic - Tukadi (Imam Ghozali); Siti Roudhotul Jannah; Sugiarto Sugiarto (CV. Creative Tugu Pena, 2022)
This article aimed to analyze the effect of social-emotional development on children's learning outcomes from 2019 until 2022. We shocked by the covid 19 virus, which requires parents to be more emotional to children and impact on children's social-emotional behavior. The research was conducted to determine the effects of social development on children's social-emotional behavior. The research used qualitative with case study approach through interviews with thematic analysis on twenty mothers who have children attending kindergarten in the East Lampung district. Using structural interview, the mothers were asked questions about the impact of children's social-emotional behavior through interviews. The results analysis shoed that that the children's socio-emotional behavior was less cooperative because children rarely play together, lack tolerance, lack socializing with friends was limited by studying at home, children's emotions sometimes feel bored and sad, children feel homesick for friends and teachers and children are also recorded as experiencing verbal violence because of the overall learning process. Keywords: Social-Emotional Development, Learning Outcomes, childhood Education